Knowledge, Attitude, and Practices Toward Snakes and Snakebites among Non-Medical College Students in Cebu, Philippines: A Mixed Method Approach - Mutya, Romel; Inocian, Edsel (Biosaintifika: Journal of Biology & Biology Education, 2024)
Understanding community perceptions and behaviors toward snakes is crucial for effective prevention and management in regions where snakebites are a public health concern. Non-medical college students, a significant demographic, can influence broader community health practices and awareness. This study aims to assess the knowledge, attitudes, and practices (KAP) towards snakes and snakebites among non-medical college students in a technological university in the fifth district of Cebu, Philippines. Employing a convergent parallel research design, quantitative data were collected through structured questionnaires, while qualitative insights were obtained via semi-structured interviews. The sample included 546 non-medical college students selected through random sampling. The findings revealed significant gaps and misconceptions, with students exhibiting moderate knowledge about snakes and snakebites. Attitudes were predominantly negative, characterized by fear and aversion. Practices concerning snakebite management needed to be revised, with many students relying on traditional rather than evidence-based methods. The study highlights considerable areas for improvement in the knowledge and practices of non-medical students regarding snakebite management, coupled with generally negative attitudes toward snakes. The novelty of this research lies in its focus on non-medical college students and specific demographics within a technological university, providing insights that can inform targeted educational interventions. Implementing educational programs to improve KAP among students is recommended, emphasizing correct snakebite first aid and fostering a more informed and balanced view of snakes. This research has significant implications for public health, suggesting that targeted education can enhance community health practices and awareness regarding snakebite prevention and management.